SISTEM PENDETEKSI POLA ISIM MUFRAD PADA CITRA AL-QUR’AN MENGGUNAKAN BINARY SIMILARITY AND DISTANCE MEASURES - Fadlisyah, Fadlisyah (Jurnal Teknologi Terapan and Sains 4.0, 2025)
The sentences in the visual representation of the Qur'an form various patterns. One of the patterns selected as the object of this study is the Isim Mufrad pattern. In this research, the Isim Mufrad pattern will be detected through image processing techniques, and subsequently, pattern class measurement will be conducted using the Binary Similarity And Distance Measures (BSDM) method. The results of the study show that the pattern detection system using Binary Similarity And Distance Measures (BSDM) through the Shape Difference formula has a detection rate ranging from 65% to 90%. This detection rate percentage indicates that the Shape Difference formula can be used as one approach for detecting similar patterns. The advantage of the Shape Difference formula is its ability to recognize patterns with a relatively small amount of reference data, making it highly suitable for implementation in such a system. Keywords: Binary Similarity And Distance Measures (BSDM), Shape Difference